Optimizing Vaccine Logistics at the Grassroots: Innovative Strategies for Effective Village-Level Immunization Programs - Ratysca, Evelyn; Ristiawanda, Novita; Aisyah, Putri Farah; Ariani, Sherly Dewinta; Humairo, Mika Vernicia (Inovasi Lokal, 2025)
The management of vaccine logistics at the village or neighborhood level is a critical component of successful vaccination programs, particularly in ensuring equitable access to vaccines. This study employed a role-playing simulation method with a participatory collaborative approach to explore the challenges and solutions in vaccine logistics management. The simulation involved 10 groups of participants, each assigned different scenarios reflecting real-world logistical issues, such as limited transportation, inadequate storage facilities, and community engagement barriers. Results showed that structured planning, supported by technological tools like real-time monitoring systems, significantly improved efficiency and reduced vaccine wastage. Community involvement emerged as another key factor, enhancing public trust and participation. However, challenges such as infrastructure gaps and digital literacy disparities persist, particularly in remote areas. Collaborative efforts among stakeholders, including governments, healthcare providers, and local communities, were identified as essential for overcoming these barriers. The findings underscore the need for integrated strategies that combine technology, training, and stakeholder collaboration to strengthen vaccine logistics at the grassroots level.